The Effect of Target Sex, Sexual Dimorphism, and Facial Attractiveness on Perceptions of Target Attractiveness and Trustworthiness - Hu, Yuanyan; Abbasi, Najam ul Hasan; Zhang, Yang; Chen, Hong (Frontiers in Psychology, 2018)
Facial sexual dimorphism has widely demonstrated as having an influence on the facial attractiveness and social interactions. However, earlier studies show inconsistent results on the effect of sexual dimorphism on facial attractiveness judgments. Previous studies suggest that the level of attractiveness might work as a moderating variable among the relationship between sexual dimorphism and facial preference and have often focused on the effect of sexual dimorphism on general attractiveness ratings, rather than concentrating on trustworthiness perception. Male and female participants viewed target male and female faces that varied on attractiveness (attractive or unattractive) and sexual dimorphism (masculine or feminine). Participants rated the attractiveness of the faces and reported how much money they would give to the target person as a measure of trust. For the facial attractiveness ratings, (a) both men and women participants preferred masculine male faces to feminine male ones under the more attractive condition, whereas preferred feminine male faces to masculine male ones under the less attractive condition; (b) all participants preferred feminine female faces to masculine female ones under the less attractive condition, while there were no differences between feminine female faces and masculine female faces under the more attractive condition. For the target trustworthiness perception, (a) participants showed no preference between masculine male faces and feminine male faces, neither under the more attractive condition nor the less attractiveness condition; (b) however, all the participants preferred masculine female faces over feminine female faces under the more attractive condition, exhibiting no preference between feminine female faces and masculine female faces under the less attractive condition. These findings suggest that the attractiveness of facial stimulus may be a reason to interpret the inconsistent results from the previous studies, which focused on the effect of facial sexual dimorphism on the facial attractiveness. Furthermore, implications about the effect of target facial sexual dimorphism on participants’ trustworthiness perception were discussed.